Evaluation of The Performance Efficiency of The Men's Clothing Factory In Najaf (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The process of economic and social development of a country requires the advancement of thereality of all economic sectors, particularly the industrial sector, through sober scientific remediesbased on ensuring the optimal use of material and human energies and allowing the best ways toexploit them and avoid waste, loss, and suffocation. Iraq's industrial sector is of exceptionalimportance because together with the agricultural sector.It is the heaviest sector of the nationaleconomy. It represents the most effective and dynamic sector in economic development through itsdirect impact on the development process and other sectors with which it is increasinglycontributing to the development process. Within the industrial sector, the manufacturing sectoremerges as an important sector that directly contributes to constructing the country's strongindustrial base, which can be relied upon in thefuture. The manufacturing sector is broad andcomplex, encompassing those industries that require the introduction or transformation of variousmechanical, chemical, natural, and compositional means to change their nature, image, and shapeand make them ready for new uses. One of the most widespread manufacturing branches is thetextile industry because of the provision of clothing and clothing to the population and theirsignificant contribution to reducing reliance on imports and the operation of national labor as laborintensiveindustries. It also has a role in increasing national income because it relies primarily ondomestic production requirements. The development and growth of textile industries, in general,requires the protection of the national product to achieve greater capacity in local markets. Themen's clothing factory in Najaf is one of the formations of the General Company for Textile andLeather Industries under the Iraqi Ministry of Industry and Minerals, characterized by its diversityof products and importance and the large production and size of capital invested in its assets. Onthis basis, the subject of the study was chosen under the title. The research aims to identify thefactory's performance efficiency level for the duration (2010 -2020) by using the performanceefficiency evaluation process criteria.